Selected morbidities among workers of a chemical processing industry in Goa - Naik, Mahika Virendra; Shailesh, Kalyani; Cacodcar, Jagadish A. (International Journal Of Community Medicine And Public Health, 2022)
Background: Exposure to various physical, mechanical, chemical hazards and unsafe practices by workers of fertiliser industries leads to many illnesses. So far not much attention has been given to occupational hazards in fertilizer industry. Therefore, the present study was undertaken to assess selected morbidities among workers in a fertilizer industry in Goa. Methods: The study was conducted over a period of November 2018 to December 2018. The data of the workers was obtained from an occupational health and safety (OHS) centre catering to a fertilizer industry in North-Goa which conducted periodic medical check-ups of the workers. The date included details regarding selected morbidities among workers of the fertilizer industry. Results: Among the workers, over one-third i.e. 104 (37.3%) were overweight and 38 (13.6%) were obese with body mass index (BMI) ≥30 kg/m2. 22 (7.9%) workers were hypertensive, 35 (12.5%) were diabetic, 46 (26.5%) had abnormal far vision and 24 (8.6%) had near vision abnormalities. Spirometry reports showed 17 (6.1%) workers suffered from mild restrictive lung disease. Assessment of audiometry reports revealed that 2 (0.8%) workers had mild hearing loss, 4 (1.6%) had moderate hearing loss and 2 (0.8%) had severe hearing loss. Conclusions: Workers in a fertilizer industry suffer from several morbidities, including the diseases like diabetes, hypertension and obesity. Apart from this, they also suffer from hearing impairment, visual impairment and conditions impairing their pulmonary functions. Periodic medical examinations are needed for timely detection and appropriate treatment of these health conditions among the workers.